(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
The study assesses the biological properties of methanolic extracts derived from the leaves, stems, and roots of Begonia malabarica, a native plant species in the mountainous area of southern India. The GC-MS was used to analyze the phytochemicals in the solvent from Begonia malabarica that had been extracted with methanol. The antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and as reference solution is ascorbic acid. The cytotoxicity activity was determined using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) approach. The GC-MS analysis effectively revealed 35 distinctive phytomolecules. The primary constituents, namely tert-butylbenzene (23%), 2-methylnaphthalene (6.2%), ethyl ester of octadecanoic acid (0.9%), and (Z,Z)-9,12-octadecadienoic acid (0.9%), are noted. The results, the methanolic extracts from B. malabarica are antioxidants that have significant levels (P < 0.05) of DPPH radical scavenging activities at different doses. The detected radical scavenging activities exhibited a higher proportion in the stem of B. malabarica. The IC50 values for the methanolic extracts were found to be 0.77 mg/ml, 0.49 mg/ml, and 0.68 mg/ml, respectively. The MTT analysis demonstrated that the methanolic extracts exhibited a considerable increase in cytotoxic activity against the pancreatic cancer (PANC-1) cell line, resulting in a cell viability percentage of 69.63% at a concentration of 31.25µg/ml. These findings confirm the possible biological effects of B. malabarica and its prospective use in different pharmaceutical pursuits in the future.